Investigating the Relationship Between Social Support and Durable Return to Work. (8th April 2015) - Watt, Bruce D.; Ford, Lucas; Doley, Rebekah M.; Ong, Sabrina; Hicks, Richard E.; Fritzon, Katarina; Cacciola, Tony
Abstract : The aim of the current study was to investigate the relationship between social support and durable return to work (RTW) post occupational injury. A total of 1, 179 questionnaires were posted to clients previously receiving vocational rehabilitation services from the Return to Work Assist program in Queensland, Australia. Participants were asked to indicate their current RTW status, in addition to completing questionnaires measuring their relationship with their superior, relationships with colleagues, and social support external to the workplace. The statistical analysis included 110 participants. An ANOVA indicated that participants in the RTW group reported significantly better relationships with their superiors and colleagues than participants in the non-durable RTW group. No significant differences were observed between the RTW, non-durable RTW and no RTW groups on a measure of social support external to the workplace. Although the findings were limited by the low response rate, an evaluation of demographics indicated the respondents were representative of the original target sample. The findings suggested that providing support in the workplace is an important area for intervention and may be a means of increasing durable RTW outcomes.